B lymphocytes transdifferentiate into immunosuppressive erythroblast-like cells - Yang, Zhe; Wang, Zheng; Wu, Lei; Wang, Ying; Xu, Zhihui; Liu, Ying; Wang, Fangfang; Yu, Duonan (Frontiers in Immunology, 2023)
Recent studies have demonstrated that a particular group of nucleated cells that exhibit erythroid markers (TER119 in mice and CD235a in humans) possess the ability to suppress the immune system and promote tumor growth. These cells are known as CD45 + erythroid progenitor cells (EPCs). According to our investigation, it appears that part of the CD45 + EPCs originate from B lymphocytes. Under hypoxia conditions, mouse B lymphoma cells are capable of converting to erythroblast-like cells, which display phenotypes of CD45 + TER119 + cells, including immunosuppressive impacts on CD8 T cells. Furthermore, non-neoplastic B cells have similar differentiation abilities and exert the same immunosuppressive effect under anemia or tumor conditions in mice. Similar B cells exist in neonatal mice, which provides an explanation for the potential origin of immunosuppressive erythroid cells in newborns. Additionally, CD19 + CD235a + double-positive cells are identified in the peripheral blood of patients with chronic lymphocytic leukemia.These aforesaid findings indicate that some CD45 + EPCs are transdifferentiated from a selective population of CD19 + B lymphocytes in response to environmental stresses, thus highlighting the plasticity of B lymphocytes. We anticipate a potential therapeutic implication that targeting a specific set of B cells instead of erythroid cells restores adaptive immunity and delays cancer progression.